Literary Archetypes: The Notion and Application - Francis, V. (Journal of Ecohumanism, 2025)
Literary criticism is a creative domain offering a new insight or perception on a piece of literature. Late twentieth century saw the emergence of many literary avant-gardes formulating ground-breaking literary hermeneutics, facilitating the reader and the writer to perceive a literary work from different perspectives. Archetypal criticism is one such theory that emerged from Frazer’s anthropological study and Jung’s analytical psychology. Frye’s Anatomy of Criticism became a landmark work on archetypal criticism. The collective unconscious commonly found among all human beings is known as archetypal patterns. This paper explores the inquisitiveness raised by noted psychologists on the working of human mind and the mystery and complexity surrounded it. The psychoanalytical views of Freud and Jung had great influence on art, literature, culture and on many others realms of humanities. This paper deeply delves into the contribution made by Jung on the working of human mind. Through his arduous study and research, he came out with a new concept called ‘collective unconsciousness’. Jung’s idea of ‘collective unconsciousness’ became the seed for archetypal criticism. Archetypal criticism examines the recurrent patterns found in the literatures of various nations and cultures; and in different ages – the patterns like themes, characters, settings, symbols, beliefs, rituals, etc. Northrop Frye was one of the prominent practitioners of archetypal criticism. He interpreted the literary archetypes with myths, religions and nature. The final part of this paper lists out the acclaimed literary works which are embedded with archetypal patterns.